Penerapan Manajemen Pasien Safety dalam Rangka Peningkatan Mutu Pelayanan di Rumah Sakit - Sri Rezeki; Ermi Girsang; Chrismis Novalinda Ginting; Ali Napiah Nasution (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the application of patient safety management to improve service quality. The method used is descriptive-qualitative. The results of the study show that there are several themes found, namely: 1) building a culture of patient safety; 2) facilities, infrastructure and monitoring; 3) risk management; 4) building a reporting system; and 5) involving the patient. In conclusion, the efforts made by the Royal Prima Medan Hospital in terms of leadership and staff support are that the directors are also responsible for management commitment. Keywords: Management, Service Quality, Patient Safety